Praktek Pemidanaan Terhadap Saksi Pelaku Tindak Pidana Yang Bekerja Sama/ Justice Collaborator (Telaah Yuridis Putusan No. 14/ Pid.B/ Tpk/ 2011/ Pn.Jkt.Pst Pengadilan Tipikor Jakarta) - Rahardian F.N, Pujiyono, Sularto (Diponegoro Law Journal, 2012)
In a discussion against corruption lately, is often heard a term whistleblower or justice collaborator, which is used by marshal apparatus as a method of revealing extermination of corruption process with giving legal protection system to the informant witness or subject witness. The essential of this legal protection is that that in the condemnation could get the least punishment for the whistleblower or justice collaborator